Three-dimensional tomographic assessment of the distances for access to superior joint space in the arthroscopy of temporomandibular joint - Sato, Fábio Ricardo Loureiro [UNESP]; Tralli, Gustavo; Araujo, Marcelo Marotta [UNESP]; Nascimento, Rodrigo Dias [UNESP]; Araldi, Fernando Vagner [UNESP]; de Moraes, Michelle Bianchi [UNESP] (Elsevier, 2025)
In recent years, the refinement and dissemination of minimally invasive techniques for the surgical management of intra-articular pathologies have gained considerable relevance within the therapeutic arsenal, chiefly owing to the reduced morbidity associated with such interventions. Despite these advantages, arthroscopic procedures are not devoid of risks, particularly because the insertion of trocars and instruments into the joint is frequently performed in a blind manner, thereby increasing the likelihood of inadvertent iatrogenic events and technical complications. In view of these limitations, the present investigation sought to undertake a tridimensional morphometric analysis based on computed tomography in order to define precise anatomical parameters for intra-articular access routes during arthroscopic interventions. For this purpose, a total of 50 computed tomography (CT) scans were analyzed, with the goal of calculating three-dimensional insertion points for arthroscopic instrumentation. These values were subsequently compared with linear reference measurements previously established in the literature, as well as between gender and across individuals stratified by obesity status. The results demonstrated minimal variation in relation to the standard anatomical references reported in prior studies, with no statistically significant differences detected between male and female individuals. However, a significant disparity was identified between obese and non-obese subjects, particularly with respect to the soft tissue thickness overlying the access site. These findings underscore the necessity of individual arthroscopic entry point planning in obese patients to account for such anatomical differences, thereby reducing the risk of access-related complications and enhancing procedural safety.